Search for dark matter produced in association with a dark Higgs boson decaying into W±W∓ or ZZ in fully hadronic final states from √s=13 TeV pp collisions recorded with the ATLAS detector - Aad, Georges; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physical review letters, 2021)
Several extensions of the Standard Model predict the production of dark matter particles at the LHC. An uncharted signature of dark matter particles produced in association with VV=W±W∓ or ZZ pairs from a decay of a dark Higgs boson s is searched for using 139 fb−1 of pp collisions recorded by the ATLAS detector at a center-of-mass energy of 13 TeV. The s→V(q¯q)V(q¯q) decays are reconstructed with a novel technique aimed at resolving the dense topology from boosted VV pairs using jets in the calorimeter and tracking information. Dark Higgs scenarios with ms>160 GeV are excluded.
Im Titel ist "±" und "∓" jeweils hochgestellt
ATLAS Collaboration: G. Aad, F. Bartels, A.E. Bolz, M.M. Czurylo, S.J. Dittmeier, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P.S. Ott, D.F.Rassloff, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, M. Wessels, X. Yue [und viele weitere]
Gesehen am 21.06.2021